Collaborative working in health and social care: Lessons learned from post‐hoc preliminary findings of a young families' pregnancy to age 2 project in South Wales, United Kingdom. (1st September 2020) - Jones, Sara W.; Darra, Susanne; Davies, Mike; Jones, Catherine; Sunderland‐Evans, Wendy; Ward, Mike R. M.
Abstract: Children of young and socially disadvantaged parents are more likely to experience adverse outcomes. In response to this, a unique young families' project in Swansea, UK, was created, which drew together a team of multi‐agency professionals, to support people aged 16–24 from 17 weeks of pregnancy throughout 1, 001 days of the child's life. The aim of the JIGSO (the Welsh word for Jigsaw) project is for young people to reach their potential as parents and to break the cycle of health and social inequality. This evaluation analysed routinely collected data held by the project from January 2017 to December 2018 exploring health and social outcomes, including smoking and alcohol use in pregnancy, breastfeeding, maternal diet and social services outcomes. Outcomes were compared to local and national averages, where available. Data relating to parenting knowledge and skills were available via records of 10‐point Likert scales, one collected at the start of the JIGSO involvement and one around 4–6 months later. Findings showed higher than average levels of breastfeeding initiation and lower smoking and alcohol use in pregnancy. Parents also reported enhanced knowledge and confidence in their child care skills, as well as improved family relationships. Parents with high levels of engagement with JIGSO also appeared to have positive outcomes with Social Services (their child's name was removed from child protection register or their case was closed to social services). This was a post‐hoc evaluation, not an intervention study or trial, and thus findings must be interpreted with caution. Despite this, the findings are promising and more prospective research exploring similar services is required.